Strategy for Utilizing Bukitinggi 2 State Senior High School as a Heritage Tourism Commodity Based on Ethics and Legality of Preservation - Apis, Muhammad Rafif Rifki Al Ghifary; Rahmad Ramadan (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
SMA Negeri 2 Bukittinggi, located in West Sumatra Province, is one of the oldest educational institutions in the region and possesses significant historical and cultural value in the development of education in Indonesia. Its designation as a Heritage School or cultural heritage school in 2022 underscores its strategic role as a guardian of educational heritage from the Dutch colonial period to the modern era. The presence of well-preserved colonial-era architecture, a school environment rich in historical meaning, and its longstanding contribution to the formation of the nation’s intellectual community position SMA Negeri 2 Bukittinggi not only as an educational institution but also as an educationally valuable cultural asset. This study aims to formulate management strategies for developing SMA Negeri 2 Bukittinggi as an ethical and sustainable heritage tourism destination without disrupting its primary educational function. The research employs a descriptive qualitative approach through literature review, field observation, and policy analysis related to cultural heritage conservation. The findings indicate that heritage tourism development can be achieved through the application of conservation-oriented principles, the strengthening of regulatory frameworks and collaboration with local governments and cultural heritage institutions, and the development of educational tourism based on the active participation of students, alumni, and the local community. Through this approach, SMA Negeri 2 Bukittinggi has strong potential to serve as a model for heritage school management in Indonesia by harmoniously integrating educational functions, cultural preservation, and educational tourism.